Increased use of security personnel in Irish psychiatric hospitals: 2008–2012. (10th April 2015) - Shannon, S.; Devitt, P.; Murphy, K. C.
Abstract : Objectives: Little is known about the involvement of security personnel in Irish psychiatric care. Content analysis of inspection reports is a feasible way to investigate this under-researched topic. We aimed to (i) Describe the number of approved centres per year in which we observed comments about the presence of security personnel in published reports of inspections conducted from 2008 to 2012 (ii) Report the main themes of all text relating to security personnel published in these inspection reports. Method: We conducted a content analysis of all 349 inspection reports published between 2008 and 2012. Results: The number of approved centres in which security personnel were noted increased from 3% to 8% between the years 2008 and 2012. This increase was not statistically significant when the same unique centres were compared between years ( p =0.684). Employment details such as contracted employment relationship, location relative to the approved centre and hours of work appeared inconsistent across centres. Role functions of security personnel differed across centres and ranged from monitoring the entrance of a unit to observing, restraining and secluding patients. Contrasting perceptions of suitability were evident in the inspection reports. The extent to which the training needs of security personnel were met was unclear from the reports. Conclusions: Activity of security personnel in psychiatric hospitals may not be role appropriate, compliant with legislation or conducive to treatment. Best practice guidelines should be developed in consultation with multiple stakeholders.